Dressing‐Shaped Rabi Oscillation of Photon Pairs in Hot Atomic Ensemble. Issue 2 (18th December 2020) - Li, Kangkang; Li, Sifan; Li, Changbiao; Cai, Yin; Li, Feng; Zhang, Yanpeng
Abstract: The nonclassical states of light serve as potential candidates for emerging quantum information processes. A quantum information unit with higher information capacity is interesting and useful in large quantum information systems, such as quantum computations. The most mature way to increase information capacity is to employ a post‐selection or cascaded method with the biphoton state and polarizing beam splitters to increase the qubits of the entangled state. Another promising processing is shaping the temporal correlations of entangled state to high‐dimensional entangled states to increase the superposed states of each qubit. Based on the photon pair state in a hot atomic ensemble, experiments are conducted to shape its temporal correlations to multi‐periodic Rabi oscillations and nonlinear phase shifts. By employing the external dressing field to quantum transitions, the nonlinear interaction produces multiple frequency modes, shaping the temporal correlation of photon pairs to multi‐periodic Rabi oscillation and proposing a 3D energy–time‐entangled qubit for photon pair state. Interestingly, the maximum peak of the periodic Rabi oscillation can migrate with a longer correlation time because of a nonlinear phase shift. Wave shaping of the photon pair state, therefore, has the potential for applications in quantum information processes with higher information capacity and quantum memory. Abstract : A novel and effective method is proposed to enhance the information capacity by shaping the temporal correlation of biphoton state as 3D energy–time‐entangled state in hot atomic vapor cell. The study focuses on the manipulation of the properties of biphoton temporal correlation, such as Rabi oscillation, frequency modes, and nonlinear phase shift, in the two‐photon coincidence counting measurements.